Propranolol for treating emotional, behavioural, autonomic dysregulation in children and adolescents with autism spectrum disorders. (June 2018) - Sagar-Ouriaghli, Ilyas; Lievesley, Kate; Santosh, Paramala J
Objectives: To date, there is no single medication prescribed to alleviate all the core symptoms of Autism Spectrum Disorder (ASD; National Institute of Health and Care Excellence, 2016). Both serotonin reuptake inhibitors and drugs for psychosis possess therapeutic drawbacks when managing anxiety and aggression in ASD. This review sought to appraise the use of propranolol as a pharmacological alternative when managing emotional, behavioural and autonomic dysregulation (EBAD) and other symptoms. Materials and methods: Sixteen reports examined the administration of propranolol in the context of ASD. Results: Sixteen reports broadly covered cognitive domains, neural correlates, and behavioural domains. From the eight single-dose clinical trials, propranolol led to significant improvements in cognitive performance – verbal problem solving, social skills, mouth fixation, and conversation reciprocity; and changes in neural correlates – improvement in semantic networks and functional connectivity. The remaining eight case series and single case reports showed improvements in EBAD, anxiety, aggressive, self-injurious and hypersexual behaviours. Additionally, propranolol significantly improved similar behavioural domains (aggression and self-injury) for those with acquired brain injury. Conclusion: This review indicates that propranolol holds promise for EBAD and cognitive performance in ASD. Given the lack of good quality clinical trials, randomised controlled trials are warranted to explore the efficacy of propranolol in managing EBAD in ASD.